Development and characterization of polypropylene waste-derived char filled sugar palm [Arenga pinnata (Wurmb) Merr.] starch biopolymer composite briquettes - Moklis, Muhammad Harussani (2021)
According to Ministry of Health Malaysia (MOH), total utilization of personal protective equipment (PPE) of healthcare workers (HCW) under the MOH is approximately 59 million units per month. PPEs comprised of facemasks, isolation gowns, hair nets and shoe covers, which mainly made of polypropylene (PP). Due to the coronavirus disease (COVID-19) epidemic, increasing PP wastes had been produced by the hospitals and isolation facilities. To counter the increasing plastic wastes production, a proper green strategy to decompose the PP wastes is needed and pyrolysis, a thermal decomposition process, is the best way to decompose and convert the wastes into useful product with lower pollutions. Thus, this work is aimed to decompose and convert PP waste into char via pyrolysis and utilized as raw materials in fuel briquette application. PP wastes collected from university healthcare centre (PKU) were then went through cleaning and washing process under the surveillance from PKU staffs. Then, the raw materials were pulverized into 0.25 mm powder. Pyrolysis with different low pyrolytic temperatures, 450, 500, 550, 600, and 650 ⁰C selected as final pyrolysis temperatures, was applied to convert disinfected PP-based isolation gown waste (PP-IG) or PP waste into an optimized amount of char yields. A batch reactor with horizontal furnace was used to mediate the thermal decomposition of PP-IG. The optimum solid pyrolysis product (char) yields at different temperature was determined. Elemental, morphological, surface area and thermal properties of the char were analysed. The results show that the amount of yielded char is inversely proportional to the temperature. Optimized temperature for maximum char yields has been recorded. The enhanced specific surface area, SBET values for the char and its pore volume were collected, ~24 m2g-1 and ~0.08 cm3g-1, respectively. The char obtained at higher temperatures display higher volatilization and carbonization. The yielded chars were then mixed with different amount of sugar palm starch (SPS) loading, 0, 10, 20, 30 and 40%, which then moulded into briquettes via hydraulic press. The mechanical, physical, morphological, thermal and combustion characteristics of char filled sugar palm starch (C/SPS) biopolymer composites were determined using compressive test, Fourier transform infrared (FTIR), field emission scanning electron microscopy (FESEM), thermogravimetric (TGA) and bomb calorimeter analysis, respectively. The results show that the compressive strength of the briquettes increased as the SPS loading increased, whereas the higher heating values (HHV) reduced. The findings indicate that C-80/SPS-20 briquettes presented excellent combustion characteristics (1,761.430 J/g) with satisfactory mechanical strength (1.463 MPa) in the compression test. Thus, C-80/SPS-20 briquettes are the most suitable composites for domestic and commercial uses. The development of such briquette char is an effort to address the ongoing environmental problems. These findings are beneficial to utilize this pyrolysis model for plastic waste management and convert PP waste into char for further C/SPS briquette biocomposite applications, with the enhanced mechanical and combustion properties, amidst COVID-19 pandemic.